Performance analysis of high temperature thermal energy storage in shallow depth enhanced geothermal system - Bu, Xianbiao; Chen, Wei; Du, Jianguo; Wang, Lingbao (Frontiers in Built Environment, 2024)
IntroductionSolar resources are rich in north China and however, solar thermal energy has little contribution to space heating due to the intermittency and instability as well as the lack of seasonal energy storage technology. Although underground thermal energy storage (UTES) can solve the above problems effectively, the existing UTES systems either have low energy storage density and recovery efficiency or have high construction cost.MethodsInspired by the enhanced geothermal system (EGS), here a novel scheme of storing high temperature thermal energy into the shallow depth EGS (SDEGS) is proposed. Thermal energy is stored into SDEGS during the non-heating season and is extracted for space heating during the heating season.ResultsThe results show the thermal performance of SDEGS always remains stable due to continuous thermal energy injection, and its thermal recovery efficiency is always greater than 90% by storing thermal energy into the tight rocks and circumventing the formation of the natural convection.DiscussionSDEGS can be constructed in the shallow buried depth rocks having a low requirement about temperature, largely reducing project cost and risk and widening the application range.